Screening of Antibacterial and Anticancer Activity of Soft Corals from Togean Islands, Indonesia - Muhammad Sulaiman Zubair; Subehan Lallo; Rusmiyanti Rusmiyanti; Arsa Wahyu Nugrahani; Ibrahim Jantan (Indonesian Journal of Pharmacy, 2018)
Soft corals (Octocorallia, Alcyonaceae) have been reported to possess diverse biological activities and unique structural chemistry. This study aims to screen the potential antibacterial and anticancer activity of some soft corals collected from Togean Islands, Central Sulawesi, Indonesia. They were Lobophytum sp, Sarcophyton sp, Sinularia sp 1, and Sinularia sp 2. All dried coral materials were extracted for 3 x 24 h by maceration method using methanol and then evaporated by rotary evaporator to obtain viscous extracts. The determination of antibacterial activity had been performed by well agar diffusion method against Staphylococcus aureus and Escherichia coli. Meanwhile, the cytotoxic activity was performed by MTT method, followed by apoptosis annexin V-FTIC assay agains. Identification for the presence of terpenoids was performed by vacuum p-anisaldehyde-sulphuric acid spraying reagent on thin layer chromatography (TLC). Sinularia sp2 extract have strongly inhibited S. aureus and E.coli with the diameter of inhibition range from 12.76mm and 17.86mm, respectively. Moreover, Sinularia sp2 extract possessed also cytotoxic activity against human breast adenocarcinoma (MCF-7) and colorectal carcinoma (HCT-116) with the IC50 of 46.807 and 47.186 μg/mL, respectively.  Extract Sinularia sp 1 was found to have strongest cytotoxicity on human colon colorectal carcinoma (HCT-116) with the IC50 of < 1.505 μg/mL. Annexin V-FTIC assay clearly exhibited that the apoptosis mechanism is proposed by the extracts of Sinularia sp1 and Sinularia sp 2. Terpenoids were identified on both  extracts suggesting for further purification and isolation for the bioactive terpenoid compounds.